Effect of 3D Printing Parameters on the Transparency of Medical Hydrogels for Corneal Stroma Fabrication - Qiang Gao; Kaicheng Yu; Youyun Shang; Zexue Lin; Min Zhu; Lihua Lu; Tao Jiang; Peng Zhang (Gels)
Medical hydrogels represent a promising solution for the treatment of corneal diseases and trauma, offering potential to address the shortage of donor corneas. To meet the functional requirements of artificial corneas in tissue engineering, it is crucial to fabricate biomimetic structures with high optical transparency using 3D printing techniques. As fiber alignment during the printing process has a pronounced impact on light transmittance, precise control of the printing parameters is essential. This study focuses on the experimental optimization of 3D printing conditions for hydrogel materials to improve their physical properties, particularly optical clarity, thereby enhancing their suitability for artificial corneal applications. Collagen derived from bovine Achilles tendons was chosen due to its excellent printability. A series of controlled experiments were conducted to systematically investigate the influence of key process parameters on hydrogel transparency. The findings enabled the identification of an optimized parameter set that significantly improved the optical properties of the 3D-printed biomimetic corneal stroma. Additionally, cell seeding and culture assays confirmed the favorable biocompatibility of the developed material.